Nicotinamide adenine dinucleotide metabolism in Candida albicans. - Chaffin, W L (1979)
The functional pathways of nicotinamide adenine dinucleotide (NAD) biosynthesis and their regulation were studied in the dimorphic fungus Candida albicans. The presence of a functional endogenous pathway of NAD biosynthesis from tryptophan was demonstrated. In addition, nicotinamide served as an efficient salvage precursor for NAD biosynthesis but nicotinate was not utilized. The pathway for nicotinamide utilization involved nicotinate and nicotinate nucleotides as intermediates, suggesting that the failure to utilize nicotinate involves a transport defect. The mechanisms that regulate NAD levels during exponential growth operated to maintain constant NAD levels when NAD biosynthesis occurred exclusively from endogenous or salvage pathways or from a combination of the two. The regulation also operated such that the salvage pathway was preferentially utilized.